The Routledge companion to twentieth and twenty-first century Latin American literary and cultural forms - De Ferrari, Guillermina, 1966-; Siskind, Mariano, 1972- (Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2023)
"The Routledge Companion to Twentieth and Twenty-First Century Latin American Literary and Cultural Forms brings together a team of expert contributors in this critical and innovative volume. Highlighting key trends within the discipline, as well as cutting-edge viewpoints that revise and redefine traditional debates and approaches, readers will come away with an understanding of the complexity of twenty-first-century Latin American cultural production and with a renovated and eminently contemporary understanding of twentieth-century literature and culture. This invaluable resource will be of interest to advanced students and academics in the fields of Latin American literature, cultural studies, and comparative literature"--
Keywords: Latin American literature -- 20th century -- History and criticism; Latin American literature -- 21st century -- History and criticism; Latin America -- Intellectual life -- 20th century; Latin America -- Intellectual life -- 21st century; FOREIGN LANGUAGE STUDY / General; FOREIGN LANGUAGE STUDY / Spanish; LANGUAGE ARTS & DISCIPLINES / General